TRIM21 inhibits irradiation-induced mitochondrial DNA release and impairs antitumour immunity in nasopharyngeal carcinoma tumour models - Li, Jun-Yan; Zhao, Yin; Gong, Sha; Wang, Miao-Miao; Liu, Xu; He, Qing-Mei; Li, Ying-Qin; Huang, Sheng-Yan; Qiao, Han; Tan, Xi-Rong; Ye, Ming-Liang; Zhu, Xun-Hua; et al. (Nature communications, 2023)
Although radiotherapy can promote antitumour immunity, the mechanisms underlying this phenomenon remain unclear. Here, we demonstrate that the expression of the E3 ubiquitin ligase, tumour cell-intrinsic tripartite motif-containing 21 (TRIM21) in tumours, is inversely associated with the response to radiation and CD8 + T cell-mediated antitumour immunity in nasopharyngeal carcinoma (NPC). Knockout of TRIM21 modulates the cGAS/STING cytosolic DNA sensing pathway, potentiates the antigen-presenting capacity of NPC cells, and activates cytotoxic T cell-mediated antitumour immunity in response to radiation. Mechanistically, TRIM21 promotes the degradation of the mitochondrial voltage-dependent anion-selective channel protein 2 (VDAC2) via K48-linked ubiquitination, which inhibits pore formation by VDAC2 oligomers for mitochondrial DNA (mtDNA) release, thereby inhibiting type-I interferon responses following radiation exposure. In patients with NPC, high TRIM21 expression was associated with poor prognosis and early tumour relapse after radiotherapy. Our findings reveal a critical role of TRIM21 in radiation-induced antitumour immunity, providing potential targets for improving the efficacy of radiotherapy in patients with NPC. The molecular mechanisms determining the response to radiotherapy remain incompletely understood. Here, the authors demonstrate that the E3 ubiquitin ligase and intracellular Fc receptor, TRIM21, impairs CD8 + T cell responses in nasopharyngeal carcinoma tumour models following ionizing radiation.